Pengaruh Sirkulasi di Area Wudhu Putri Terhadap Privasi Penggunanya - Faiqoh Roshwah Salsabila,; Budi Sudarwanto , (Nature: National Academic Journal of Architecture, 2024)
High privacy is essential in women's ablution areas. This is because women must remove or lower their headscarves slightly during ablution. There are five implementation options for achieving privacy, one of which is spatial arrangement and access. Circulation is needed as a connecting access between spaces. Good circulation requires clear signage. There are many opinions regarding the comfort of circulation in mosques that require gender-based area separation, but deviations are still found in implementation. This study aims to find out how circulation affects the privacy comfort of users in women's ablution areas. Therefore, this study uses a descriptive quantitative method using questionnaires filled out by at least 30 female respondents at each research object. The data obtained is then described and compared with existing theories. The results found that the circulation flow affects the privacy comfort of users in women's ablution areas, including signage facilities as a supporter of the existence of the circulation flow. Signage and the design of room dividers that separate between male and female areas have a significant impact on the privacy comfort of users of the women's ablution area. Clear signage will create good circulation and make user privacy more secure. Therefore, it is important for designers to pay attention to the separation of areas between men and women.